L'Accademia in viaggio: Il tour italiano degli architetti danesi tra Settecento e Ottocento - Esposito, Monica (UrbsHistoriaeImago, 2021)
The founding of Det Kongelige Danske skildre- bildhugger og Bygnings akademi marks a watershed in the education of Danish architects, and a renewal in architectural production between the 18th and 19th centuries. Throughout the two centuries, a young Danish architect's formative experience is linked to study at the Academy, which, on a continuous basis, updates, conforms and takes part in contemporary diatribes, theories and speculations. The volume reconstructs the paths and investigations made in Italy by Danish stipendiaries and their participation in contemporary debates. What emerges is a Copenhagense society strongly linked to the Peninsula; in fact, traveler-architects between the 18th and 19th centuries identified Italian buildings as having national identity roots. Thanks to largely unpublished archival material, we come to understand the fascination that Italy has on Danish travelers, who will continually attempt to recreate a Lidt Italien in the cold Nordic lands.